2005
DOI: 10.1007/s00383-005-1563-x
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous congenital band: a rare cause of intestinal obstruction and failure to thrive

Abstract: Intestinal obstruction caused by an anomalous congenital band is very rare in adults and children. A 7-year-old boy was admitted with acute intestinal obstruction. His parents mentioned that the child always had mild abdominal distention and failure to thrive from his infancy. On his medical history, there were not any attacks of abdominal pain, fever and hospitalization. Laparotomy showed an ileal loop compressed by an anomalous band, which extended from the ileum to the sigmoid mesentery resembling a mesente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 5 publications
1
20
0
8
Order By: Relevance
“…An SBO caused by a congenital band is an exceedingly rare condition and, thus, the incidence is unclear. Our literature review found only 32 reported cases of congenital bands, and only one was reported in an emergency medicine journal (5)(6)(7)(8)(9)(11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 87%
“…An SBO caused by a congenital band is an exceedingly rare condition and, thus, the incidence is unclear. Our literature review found only 32 reported cases of congenital bands, and only one was reported in an emergency medicine journal (5)(6)(7)(8)(9)(11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 87%
“…On the other hand, a congenital band may be explained as remnants of ventral mesenterium that failed to reabsorb completely past the fourth week of gestation [2]. A congenital band can be single vascular band or multiple dense or adhesive bands like our case [6][7][8][9]. According to previous related reports in the literatures, terminal ileum is the most common at the level of obstruction [4,6,7,[10][11][12].…”
Section: Discussionmentioning
confidence: 97%
“…A congenital band can be single vascular band or multiple dense or adhesive bands like our case [6][7][8][9]. According to previous related reports in the literatures, terminal ileum is the most common at the level of obstruction [4,6,7,[10][11][12]. SBO is mostly caused by compression of the bowel by the band, and may develop in case that intestinal loop is trapped band and the mesentery [2,12].…”
Section: Discussionmentioning
confidence: 99%
“…Em medicina, adesões anômalas são causas extremamente raras de defeitos congênitos obstrutivos, não havendo referência de sua ocorrência em medicina veterinária (BERROCAL et al, 1999a;ETENSEL et al, 2005). Com o presente trabalho, objetiva-se expor um caso de obstrução intestinal congênita causada por adesão de alça no púbis em uma cadela, situação nunca antes descrita em medicina veterinária.…”
unclassified
“…O animal em questão apresentava, além de vômito, apatia e distensão abdominal com aumento do peristaltismo, emagrecimento progressivo e falha no desenvolvimento, sinais também descritos por ETENSEL et al (2005).…”
unclassified